Place attachment and attitude towards changes and improvement of the traditional shopping streets in the city centre of Kuala Lumpur. - Ujang, Norsidah (2012)
The main streets reflect the image of a city and represent the people’s perception of its identity. As a result of constant and long term engagement, the streets are also imbued with meanings and attachment. This paper addresses people’s attitudes towards changes of the traditional shopping streets in light of place attachment dimensions. The findings are based on field surveys conducted with 220 respondents who are familiar with the streets and face to face interviews with 24 respondents who work and stay in the area. The findings demonstrate mixed responses from the traders and shopowners with regards to changes. The improved streetscape has been positively valued by shoppers and visitors. Concerns include the quality of public facilities, vehicular and pedestrian accessibility, safety, sustainability of economic activity, social interference, the undermining of meaningful buildings and the diminishing of goods of particular interest. Users who had longer period of engagement in the area are more protective about the streets’ livelihood and more sensitive towards new physical intervention. For future improvement, the need is to ensure that changes and intervention will not discourage users’ daily engagement and should not threaten their attachment to the streets. This can support the psychological well-being of the people who regard the streets as places of personal, economic and socio-cultural significance.